(untitled) (Heritage, 2024)
In this paper, on the basis of empirical research, the conditions, perspectives and possibilities of replacing the dollar as the world’s leading currency will be presented in a systematic and methodological way. In this sense, the paper follows the positioning of the dollar as the primary currency used for international reserves in the world. The presentation of the dollar as a reserve currency follows the comparison with other currencies and gold as well as the increase in the share of other currencies. In the paper, the potentials of the world’s leading economies and BRICS countries were developed and presented through comparative analysis, with a presentation of research results and the potential of de-dollarization.